Dominating Attributes Of Professed Firm Culture Of Holding Companies – Members Of The Bulgarian Industrial Capital Association - Kiril Dimitrov; Marin Geshkov (Economic Alternatives, 2018)
This article aims to outline the diversity of cultural phenomena that occur at organizational level, emphasizing the place and role of the key attributes of professed firm culture for the survival and successful development of big business organizations. The holding companies, members of the Bulgarian Industrial Capital Association, are chosen as a survey object as the mightiest driving engines of the local economy. That is why their emergence and development in the transition period is monitored and analyzed. Based on an empirical study of relevant website content, important implications about dominating attributes of professed firm culture on them are found and several useful recommendations to their senior management are made.
Keywords: L20; M14; 330; organizational culture; firm culture; corporate culture; professed culture